Development of Gelatin/Zein Electrospun Nanofiber Films Containing Purple Sweet Potato Anthocyanin for Real-Time Freshness Monitoring of Aquatic Products - Wang, Chenyu; Huang, Aixia; Fang, Jiaxuan; Li, Shuangdie; Wu, Siyu; Sun, Di; Ma, Qingbao; Yu, Zhongjie; Liu, Yu; Jiang, Wei (Coatings (Basel), 2025)
In the present study, an electrospinning freshness monitoring film prepared by gelatin/zein loading with purple sweet potato anthocyanins (PSPA) was produced to track the freshness state of Penaeus vannamei. The electrospun nanofiber films with the gelatin and zein weight ratio of 1:0, 3:1, 2:1, and 1:1 were named GA, GZA 3:1, GZA 2:1, and GZA 1:1, respectively. The impacts of zein concentration on the electrospun nanofiber film properties were investigated. SEM results showed that a smooth surface was observed for the electrospun nanofiber films. As the zein content increased, the average diameter decreased. No new characteristic peaks were shown by FTIR and XRD, indicating the good compatibility between gelatin, zein, and PSPA. The incorporation of zein decreased the swelling ratio (from completely dissolved to 100.7%) and water solubility (from 100% to 30%) and increased the water contact angle (from 0° to 113.3°). The GA, GZA 3:1, GZA 2:1, and GZA 1:1 had apparent color changes to NH3 and demonstrated good stability and reversibility. Furthermore, the freshness states (fresh, sub-fresh, and spoiled) of Penaeus vannamei storage at 4 °C could be effectively distinguished by GZA 3:1 by showing different colors (from pink to grayish purple to blue). Consequently, GZA3:1 exhibited improved hydrophobicity and pH sensitivity and has great potential in real-time monitoring of aquatic product quality.